Deep neck space infections: an upward trend and changing characteristics - Jarno Velhonoja; Meira Lääveri; Tero Soukka; Heikki Irjala; Ilpo Kinnunen (Springer, 2022)
Purpose This study reviews our experience with deep neck space infections (DNIs) requiring surgical intervention, includingcervical necrotizing fasciitis. The aim of the study was to identify predisposing and aggravating factors of the disease andrecognize the possible factors that can lead to life-threatening complications and slow down the healing process.
Methods We compare the results to previous data from 1985 to 2005 to fnd possible alterations and changing trends. Thecharacteristics of four lethal cases are described. This retrospective analysis includes patient data from 2004 to 2015 intertiary referral hospital and in total, 277 patients were found.
Results Surgical drainage through a neck opening±intraoral incision was made in 215 (77.6%) patients, an intraoral incision was only made in 62 patients (22.4%). ICU care was needed in 66 (23.8%) cases. Odontogenic etiology (44.8%) wasthe most common origin. The most common comorbidity was a psychiatric disorder and/or dementia and occurred in 55(19.9%) patients. Patients with underlying illnesses were more likely to be admitted to the ICU (p=0.020), required a longerICU stay (p=0.004) and repeated surgery (p=0.009). Gas formation seemed to be predictive of a more severe course ofinfection. Early extraction of the odontogenic foci was related to a lower length of stay (LOS) (p=0.039).
Conclusion The annual numbers have risen from 14 to 24 cases per year when compared to previous data. DNIs remain cause of lethal complications; the mortality was 1.4% and overall complications occurred in 61 (22.0%) patients.